A comprehensive retrospective cohort study of the journey of B-cell lymphoma in Taiwan - Pei, Sung-Nan; Wang, Ming-Chung; Ma, Ming-Chun; Kuo, Ching-Yuan; Liao, Chun-Kai; Qiu, Hong; Rothwell, Lee Anne; Liu, Yanfang (Scientific Reports, 2021)
Complete disease journey and risk factors for poor outcomes are needed to facilitate effectiveness evaluations of new therapies and clinical decision-making in B-cell Non-Hodgkin lymphoma (B-NHL), particularly in Asia where such data are lacking. This retrospective cohort study used electronic medical records from a regional medical centre in southern Taiwan to follow-up 441 patients newly diagnosed with common B-NHL subtypes: Diffuse Large B-cell Lymphoma (DLBCL), Follicular Lymphoma (FL), Chronic Lymphocytic Leukaemia/Small Lymphocytic Lymphoma (CLL/SLL), Marginal Zone Lymphoma (MZL), Mantle Cell Lymphoma (MCL), and Waldenström macroglobulinemia (WM), between 01-Jan-2008 and 31-Dec-2013, until 31-Dec-2017. Treatment pathways were modelled using a Markov approach. Stage III/IV disease at diagnosis was frequent for patients with DLBCL, FL, MCL and WM. Hepatitis B surface antigen/hepatitis C virus seropositivity was 18.6%/12.3%. Clinical responses to 1st-line treatment were observed in 76.0% (DLBCL), 87.3% (FL), 86.0% (MZL), 60.0% (MCL), and 42.9% (WM) of patients. For DLBCL, disease control was achieved by ~ 50% after 1st-line, ~ 24% after 2nd-line, ~ 17% after 3rd-line. Patients with Stage III/IV DLBCL or age > 65 years at diagnosis had lower rates of active treatment, poorer disease control and higher mortality than patients with early stage disease or age ≤ 65 years. Disease flare < 6 months after 1st-line treatment was significantly associated with mortality. Despite good clinical response rates for some sub-types, survival remains poor. New treatments are needed to improve the outcome of B-NHL.